Increased Insensible Water Loss Contributes to Aging Related Dehydration - Dmitrieva, Natalia I. (Public Library of Science, 2011)
Dehydration with aging is attributed to decreased urine concentrating ability and thirst. We further investigated by comparing urine concentration and water balance in 3, 18 and 27 month old mice, consuming equal amounts of water. During water restriction, 3 month old mice concentrate their urine sufficiently to maintain water balance (stable weight). 18 month old mice concentrate their urine as well, but still lose weight (negative water balance). 27 month old mice do not concentrate their urine as well and lose even more weight than the 18 month old mice, indicating a larger negative water balance. Negative water balance in older mice is accompanied by increased vasopressin excretion, providing further evidence of dehydration. All 3 groups maintain water balance while consuming only the water in gel food containing 56% water. However, both older groups excrete a smaller volume of urine of higher osmolality, indicating greater extra urinary water loss. Since their feces also contain less water, the excess water lost by the older mice apparently is through other routes, presumably insensible loss through the respiratory tract and skin. The greater insensible water loss occurs at an earlier age (18 months) than decreased urine concentrating ability (27 months). We propose that insensible water loss through skin and respiration increases with age, making a major contribution to aging related dehydration.